Latency, sleep hours, and blood pressure in hospitalized patients in Mexico - María Elena Pérez-Vega; Ma. Elena Aguirre-González; Tania Amaro-Valdez; Edgar Noé Morelos-García; Eunice Reséndiz-González; Ricardo Lara-Pérez (Revista Cuidarte)
Introduction: Multiple studies have associated sleep duration and quality with changes in blood pressure in the general population, considering it a related risk factor. However, there is limited information regarding hospitalized patients who tend to experience sleep disturbances. Objective: To examine the relationship between subjective sleep duration, sleep latency, and systolic and diastolic blood pressure in hospitalized patients. Materials and Methods: A cross-sectional study included 381 Mexican adults hospitalized in a secondary-level hospital in Tampico, Tamaulipas, Mexico. Self-reported sleep duration and latency were assessed using the Pittsburgh Sleep Quality Index component. Clinical and sociodemographic data were collected. The study was approved by an ethics committee. Results: In adjusted models, a significant negative association was found between subjective sleep hours and diastolic blood pressure (β= -0.59; 95% CI: -1.80 to -0.10). A significant positive relationship was observed between sleep latency and systolic blood pressure (β= 1.48; 95% CI: -0.49 to 2.47). Discussion: The findings are consistent with those of previous studies. Hospitalization can impact sleep due to unfamiliar environments, noise, irregular schedules, and invasive procedures, affecting patients' health and prognosis. Conclusions: It is essential to consider sleep as a modifiable factor in preventing and managing hypertension in hospitalized patients and to find effective interventions to improve sleep duration and quality.